Defender’s right to participate in investigative and other procedural actions under the law of the Azerbaijan Republic - Aliyev , Aydin Jamil oglu (Journal of the Belarusian State University. Law, 2021)
The article is devoted to the study of problems associated with the exercise of the right of a defender to participate in investigative or other procedural actions carried out by the body conducting the criminal process, as provided for in art. 92.9.3 of the Criminal Procedure Code of the Republic of Azerbaijan. As a result of the study, the author concludes that the text of this article does not meet the relevant requirements. The reason is that the text of the article has an inaccessible language style and content. In order to eliminate the identified problems, the author considers it appropriate to remove from the text of art. 92.9.3 of the of Criminal Procedure Code of the Republic of Azerbaijan expresses «on the proposal of the body conducting the criminal process to participate in investigative or other procedural actions carried out by this body», taking into account the proposed changes, give the specified article in a new edition, and thereby determine the right of the defender to participate in all investigative and other procedural actions carried out with the participation of his client.
Keywords: criminal trial; investigative actions; other procedural actions; defender; rights of a defender; participation in proceedings